EVALUATION OF PUSPA AGRO CENTRAL BUSINESS MARKET LOCATION IN EAST JAVA PROVINCE USING CENTER GRAVITY MODEL - Ahmad Faathir Wicaksono; Ratna Handayani (Universitas Islam Malang, 2021)
The Puspa Agro central business market was built to increase the food supply as well as shortened the supply chain to elevate the farmer income and in the large scale escalating the economic growth of East Java Province. Meanwhile, the central market operational activity did not work as expected as planned and the government initiates to upgrading the accessibility toward the Puspa Agro central market by constructing a new road connecting with the toll road directly the arterial road. The main purpose of this research is to evaluate the location of Puspa Agro central business market using the center gravity model. The research shows that the location of Puspa Agro central business market is not fulfilling the requirement based on the 3 (three) approach which are the location of people an d goods mobility, the location of agriculture production such as, fishery, fruit and vegetables and the number of the population of the nearest city. The three alternates location is proposed, at Waru and Candi districts in Sidoarjo City and near the Pasuruan City. The alternate location must be considered to rise the central business market income since the existing location was not fully capable to achieve the trading transaction.